Ecological, Economic, and Medical Roles of Fungi: Insights from Mycology in Addressing Global Challenges" - Dr. V. Basil Hans (International Journal of Fungi, 2025)
The large and diverse kingdom of fungi is vital to ecosystems, industry, agriculture, and medicine. Due to its ecological and biotechnological value, mycology has grown in importance. Fungi are crucial to natural systems and human life, decomposing organic materials, developing mutualistic interactions with plants, and producing antibiotics and fermented products. Recent advancements in molecular biology and genomics have significantly enhanced our understanding of fungal diversity, physiology, and evolutionary processes. These discoveries have unveiled previously unknown species and biochemical pathways, many of which hold promising potential for various applications. Through these cutting-edge techniques, researchers have been able to gain deeper insights into the complex biological functions of fungi, revealing their vast genetic diversity and adaptive capabilities. This article delves into the multifaceted roles of fungi, exploring their ecological contributions to ecosystems, their economic significance in industries such as agriculture and biotechnology, and their medical importance, particularly in the development of pharmaceuticals. Furthermore, it highlights the growing body of mycological research aimed at addressing critical global challenges, including food security, climate change, and the increasing issue of drug resistance. As the understanding of fungal biology expands, the potential for fungi to provide solutions to these pressing issues becomes ever more evident.
Keywords: Molecular biology; Mushrooms; fungal diversity; heterotrophic yeast; mycology